-2k+3k-6+4k=

Simple and best practice solution for -2k+3k-6+4k= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2k+3k-6+4k= equation:


Simplifying
-2k + 3k + -6 + 4k = 0

Reorder the terms:
-6 + -2k + 3k + 4k = 0

Combine like terms: -2k + 3k = 1k
-6 + 1k + 4k = 0

Combine like terms: 1k + 4k = 5k
-6 + 5k = 0

Solving
-6 + 5k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 5k = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 5k = 0 + 6
5k = 0 + 6

Combine like terms: 0 + 6 = 6
5k = 6

Divide each side by '5'.
k = 1.2

Simplifying
k = 1.2

See similar equations:

| 1+2d=-7 | | 376a+12=280a+15 | | -59+10x=53+3x | | 3x-30x+12=6 | | (3b-7)(b-7)=0 | | 18-1/28(3x)=12-1/28(2x) | | x/7+11=15 | | 2(2X)+2(180-2X)=360 | | (6x-5)(2x-3)=0 | | 6x-8+3x=3+9x-11 | | 144x^2+12=48 | | (6x-5)(2x-5)=0 | | 2(4k+2)-15k+6+2= | | 4x-(5x+3)=9x-33 | | (-8)(2)(5)= | | -3(p-10)-6(5-3p)= | | y+3/2y+5/4=-5/7(y-3/4) | | 3X+162/6-X=258 | | 3(x+2)=2x+x+6 | | 2a+42=-26 | | X=333-2x | | 3x^2=11x+4 | | 7+(1+5n)+6+24n=13 | | 28=10+(-6x) | | 6x+2y-9(5x-4y)= | | -4(3y-10)+3(2y+7)= | | -15+7x=20 | | 25-(3x+2)=2 | | (8y-3)(2y+1)=0 | | 2x+2=3x-men | | 1/8(5y+65)=1/4(20+2y) | | x+3x+x/2-225 |

Equations solver categories